2018
DOI: 10.1001/jama.2018.5725
|View full text |Cite|
|
Sign up to set email alerts
|

Association Between Oxygen Saturation Targeting and Death or Disability in Extremely Preterm Infants in the Neonatal Oxygenation Prospective Meta-analysis Collaboration

Abstract: In this prospectively planned meta-analysis of individual participant data from extremely preterm infants, there was no significant difference between a lower Spo2 target range compared with a higher Spo2 target range on the primary composite outcome of death or major disability at a corrected age of 18 to 24 months. The lower Spo2 target range was associated with a higher risk of death and necrotizing enterocolitis, but a lower risk of retinopathy of prematurity treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
168
4
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 336 publications
(193 citation statements)
references
References 41 publications
2
168
4
5
Order By: Relevance
“…In the last 3 years, little has changed in terms of refining previous recommendations for oxygen saturation targeting based on data from the NeOProm collaboration [83]. Targeting lower saturations (85–89 vs. 91–95%) reduces risk of severe retinopathy of prematurity (ROP) but at expense of increasing mortality (relative risk [RR] 1.17; 95% confidence interval [CI] 1.04–1.31) and NEC.…”
Section: Oxygen Supplementation Beyond Stabilisationmentioning
confidence: 99%
“…In the last 3 years, little has changed in terms of refining previous recommendations for oxygen saturation targeting based on data from the NeOProm collaboration [83]. Targeting lower saturations (85–89 vs. 91–95%) reduces risk of severe retinopathy of prematurity (ROP) but at expense of increasing mortality (relative risk [RR] 1.17; 95% confidence interval [CI] 1.04–1.31) and NEC.…”
Section: Oxygen Supplementation Beyond Stabilisationmentioning
confidence: 99%
“…The role of oxygen toxicity in the development of BPD has been shown in both experimental models as well as in clinical trials [22, 23]. …”
Section: Changes In the Pathogenesis Of Bpdmentioning
confidence: 99%
“…Therefore, the monitoring of supplemental oxygen is very important; in preterm infants it is performed measuring the oxygen pulse saturation (SpO 2 ). Although many studies have been carried out, the debate over whether low (85‐89%) or high (91‐95%) SpO 2 target is better remains open: the low target increases mortality and the risk of necrotizing enterocolitis and the high target increases the risk of ROP . Recently, the American Academy of Pediatrics suggested that a 90‐95% SpO 2 represents a reasonable target in substantial agreement with European guidelines that suggest a 90‐94% SpO 2 target …”
Section: Introductionmentioning
confidence: 97%